2015
DOI: 10.1371/journal.pone.0140697
|View full text |Cite
|
Sign up to set email alerts
|

Propionyl-L-Carnitine Enhances Wound Healing and Counteracts Microvascular Endothelial Cell Dysfunction

Abstract: BackgroundImpaired wound healing represents a high cost for health care systems. Endothelial dysfunction characterizes dermal microangiopathy and contributes to delayed wound healing and chronic ulcers. Endothelial dysfunction impairs cutaneous microvascular blood flow by inducing an imbalance between vasorelaxation and vasoconstriction as a consequence of reduced nitric oxide (NO) production and the increase of oxidative stress and inflammation. Propionyl-L-carnitine (PLC) is a natural derivative of carnitine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
25
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 69 publications
4
25
0
Order By: Relevance
“…ROS are produced by several enzyme systems, including Nox, xanthine oxidase, endothelial nitric oxide synthase, lipoxygenases, and myeloperoxidase . Scioli et al reported that propionyl‐L‐carnitine reduced Nox‐mediated oxidative stress and improved rat skin flap viability . The present study showed that NO‐NIF decreased p22phox protein expression.…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…ROS are produced by several enzyme systems, including Nox, xanthine oxidase, endothelial nitric oxide synthase, lipoxygenases, and myeloperoxidase . Scioli et al reported that propionyl‐L‐carnitine reduced Nox‐mediated oxidative stress and improved rat skin flap viability . The present study showed that NO‐NIF decreased p22phox protein expression.…”
Section: Discussionsupporting
confidence: 62%
“…Actually, use of superoxide dismutase (SOD), an endogenous scavenger of the superoxide radical, increased flap survival . Other antioxidative drugs have also successfully been applied to protect against flap necrosis in animal models …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is already known that the oxidative stress induces cell damage, lipid, protein, and nucleic acids oxidation [66, 67]. It is recognized that cutaneous trauma increases the tissue oxidative stress in the wounded area [66–69]. Although reactive species are able to activate cell signaling pathways and stimulate cell proliferation, differentiation, and neoangiogenesis, excessive production of these molecules inhibits the healing process, especially by inducing cell death and molecular damage in the extracellular matrix [23, 70, 71].…”
Section: Discussionmentioning
confidence: 99%
“…However, from all analyzed studies, only 15% investigated the oxidative status. This is a surprising finding, since the antioxidant effect is a pivotal mechanism indicated in several studies to support the applicability of plant extracts in the treatment of tissue damage, including skin wounds [66–69]. Another fundamental result on the cutaneous repair process is the restoration of the biomechanical properties, especially the tensile force of the newly formed tissue, which provides functional estimates on the quality of the healing process [37].…”
Section: Discussionmentioning
confidence: 99%